SISTEM KONTROL LEVEL TANKI COOKING OIL MENGGUNAKAN SCADA GUNA MENINGKATKAN EFESIENSI MONITORING - Lenni, Lenni; Gumilang, Fajar; Mubarok, Rizki (Jurnal Teknik Elektro, 2025)
The implementation of a cooking oil tank control system using SCADA (Supervisory Control and Data Acquisition) is an important step in improving monitoring efficiency in the food industry. SCADA has advanced monitoring features, which can accurately monitor oil levels, temperature, pressure, and other key parameters, as well as become an automatic regulator to optimize oil use and maintain its quality with an integrated purification system. Thus, the implementation of a cooking oil tank control system using SCADA not only improves monitoring efficiency, but also reduces the risk of machine breakdown and optimizes the use of resources, resulting in more efficient and controlled operations in the food industry.